Medsebojno delovanje zdravil pri starostnikih - Trontelj, Jurij (Farmacevtski vestnik, 2010)
Elderly patients commonly suffer from comorbidities and often take 4 or more drugs simultaneously. Polypharmacy poses a significant risk for drug-drug interactions. Elderly patients tend to eliminate drugs more slowly and they are more sensitive to drugsć adverse effects at the same time. The most important consequences of drug drug interactions that often require hospitalization are gastrointestinal bleeding, acute bradicardia, hypotension,arrhythmias and falls associated with use of psychotropic medications. In this article, 30 most commonly prescribed medications for elderly people in Slovenia are reviewed for clinically relevant drug-drug interactions using Lexi-Comp and Drugs.com databases and some Summaries of Product Characteristics. For every identified drug-drug interaction, there is an assessment of its clinical impact, an explanation of underlying mechanism and a proposition for patient management to avoid adverse effects. This article should provide valuable information for pharmaceutical interventions and bring improvements to safety and efficacy of pharmacotherapy in elderly.
Keywords: drug; interakcije; polifarmacija; starostniki; zdravila